The business of policy: a review of the corporate sector's emerging strategies in the promotion of education reform. Issue 2 (15th March 2021) - Fontdevila, Clara; Verger, Antoni; Avelar, Marina
ABSTRACT: This paper examines the increasingly diverse range of roles played by the corporate sector in shaping education policy. While a growing body of scholarship has documented the deepening embeddedness of the corporate sector within policy-making processes, empirical research on the strategies mobilized by corporate actors remains unsystematised and fragmentary. Furthermore, existing categorizations of corporate policy-influence strategies are frequently restricted to a limited group of Anglo-Saxon countries and, consequently, are ill suited to capturing emerging policy dynamics globally. Building on the results of a literature review, this paper categorises four emerging strategies articulated by the corporate sector: knowledge mobilization, networking, engaging with grassroots, and leading by example. Each strategy is illustrated with examples from a selection of country case studies. These examples suggest that, in the education policy domain, the corporate sector operates not only as a policy influencer, but increasingly as a policy actor organically embedded within policy-making processes and spaces.